Continuous terbinafine and pulse itraconazole for the treatment of non-dermatophyte mold toenail onychomycosis. (3rd April 2021) - Shemer, Avner; Gupta, Aditya K.; Kamshov, Shoni; Babaev, Meir; Hermush, Vered; Farhi, Renata; Daniel, C. Ralph; Foley, Kelly A.
Abstract: Introduction: Although dermatophytes are considered the predominant causative organisms in onychomycosis, non-dermatophyte mold (NDM) infections may be more prevalent than originally thought and may be more difficult to treat. There are limited data of oral antifungal efficacy in treating NDM onychomycosis. Method: A retrospective chart review (2009–2016) was conducted in patients receiving continuous oral terbinafine or pulse itraconazole for toenail onychomycosis due to NDMs. Mycology results and percent nail affected were recorded with patient characteristics including demographics and concurrent diseases. Complete, clinical, and mycological cure were tabulated. Results: Data from 176 patients were collected. Mycological and complete cure rates for terbinafine (69.8% and 17%) and itraconazole (67.5% and 22%) were not significantly different from each other. Regardless of oral treatment, age ( p  = .013), baseline severity ( p  = .016), and presence of atherosclerosis ( p  = .040) or hyperlipidemia ( p  = .033) decreased the likelihood of mycological cure, while age decreased the likelihood of complete cure ( p  = .001). Conclusion: Continuous terbinafine and pulse itraconazole were similar in efficacy for curing NDM onychomycosis. Age was the most consistent prognostic factor affecting likelihood of cure, with factors that may influence drug reaching the site of infection also decreasing likelihood of mycological cure.